Are Parent Education Level Have Influence to Choose First Facility / Helper for Fracture in Children with Osteogenesis Imperfecta - Yoyos Ismiarto; Doddi Putra Pratama Sudjana; Mahyudin; Sultan Agung Lumban Tobing; Anggrian; Wemdi Priya Prasetya; Adriel Benedict (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Introduction: Osteogenesis Imperfecta (OI) disease can develop fractures with or without trauma. Initial management of fracture cases depends on the patients' parents and it may affect the results. Various kinds of factors can influence parents' decision making in health issues, one of which is the level of education. Methods: This research was conducted by analyzing the results of the questionnaire for the parental education level. Patients that fulfilled the inclusion criteria were part of the study from January to March 2020. Results: The data showed that 38 (31%), 31 (26%), 29 (24%), and 23 (19%) patients were treated by bonesetters, hospitals, primary health care centers, and private clinics. There were 38 (31%) parents who took their children to bonesetters, mostly have intermediate education level. Mostly parents with high level of education bring their children treated in hospitals (49%). There was a significant correlation between their education level (P = 0.000) regarding decision making in the first fracture case. Conclusion: The parents' educational level of patients diagnosed with OI affects decision making in determining the first treatment facility for managing cases of fracture. Practice Implication : Parental education level plays an important role in making appropriate decisions for medical treatment